TENDENCIES OF CLIMATE CHANGES FOR THERMAL CONDITIONS IN THE COASTAL WATERS OF THE WESTERN BERING SEA AND ADJACENT AREAS IN THE LAST DECADES - I. D. Rostov; E. V. Dmitrieva; A. A. Vorontsov (Известия ТИНРО)
The sea surface temperature (SST) variability in recent conditions of climate warming is analyzed for the coastal waters in the western Bering Sea and adjacent areas on the data of regular observations on coastal hydrometeorological stations in 1980–2016 and the data of NOAA_OI_SST_V2 reanalysis, taking into account the climate indices variations. The data series are analyzed using the methods of Empirical Orthogonal Functions, cluster analysis, and correlation analysis. Mean climatic trends are estimated for the air temperature as +0.27 о C/decade and for SST as +0.23 о C/decade; they explain 27 % and 35 % of the year-to-year variability, respectively. The warming patterns are not identical for all seasons and areas. The most rapid growth of the air temperature and SST is observed for warm season (on average +0.36 o C/decade and +0.49 o C/decade). Both year-to-year fluctuations of SST and its climatic trend increase from south to north, the SST trend has increased from 0.11 to 0.32 o C/decade. Statistically significant climatic trends are found also in the changes of zonal and meridional components of wind velocity and certain indices of atmosphere circulation.